Insulin sensitivity obtained from the oral glucose tolerance test and its relationship with birthweight - Dallar, Yıldız (Ann Saudi Med, 2007)
BACKGROUND: Glucose intolerance and insulin sensitivity in preadolescent children might predict the risk of developing type 2 diabetes mellitus in adult life in small for gestational age (SGA) children. We aimed to investigate whether reduced birthweight is related to low insulin sensitivity in preadolescence. SUBJECTS AND METHODS: Twenty-five SGA children and 29 appropriate for gestational age children (AGA) children born between 1993 and 1994 were evaluated for insulin sensitivity in preadolescence. At the beginning of the study, body mass index (BMI) was calculated and an oral glucose tolerance test (OGTT) was performed. Blood samples to measure glucose and insulin were taken every 30 minutes during OGTT. Homeostasis of model assessment-insulin resistance (HOMA-IR) and composite index (CI) values were measured to assess insulin sensitivity. RESULTS: On the OGTT, 120-minute glucose and insulin levels were higher in SGA than AGA children (P=0.02 and P=0.001, respectively). Although there was no difference between HOMA-IR values, the mean CI value was lower in SGA than AGA children (P=0.001). There was an inverse correlation between birthweight and 120-minute glucose concentrations (r=−0.30, P=0.02). This correlation was stronger between birthweight and 120-minute insulin concentrations (r=−0.50, P=0.001). BMI was positively correlated with 120-minute insulin (r=0.50, P=0.001). There was no relationship between HOMA-IR values and birth size, but the CI index was positively correlated with birthweight (r=0.40, P=0.002). CONCLUSIONS: Birthweight may be a predictive factor for insulin sensitivity and CI is more reliable than HOMA-IR to assess this sensitivity in preadolescence.